Retificador híbrido trifásico com fator de potência unitário, alta densidade de potência e ampla faixa de regulação de tensão no barramento em corrente contínua para conexão em microrredes - Rodrigues, Danillo Borges (2016)
This work presents the analysis and the experimental development of a topological structure of three-phase hybrid rectifier, which provides operational characteristics for imposing sinusoidal input line currents, with high power factor, low current total harmonic distortion and providing a DC bus with regulated voltage using the innovative technique of Series Voltage Compensation in the DC Bus for both normal conditions of mains power supply and for temporary sags for balanced and unbalanced voltage ac power supply conditions. In order to corroborate the exposed theory and with computational simulation analysis, a 5 kW prototype was assembled and experimental tests were conducted in laboratory. The results demonstrated that under normal conditions of AC mains supply the proposed solution ensures harmonic distortions about 2 % for the input AC currents and a power factor per phase approximately unitary (0.996). Moreover, the prototype can regulate and maintain the DC bus voltage in a constant value even during the transient caused by a high-power load step. During the occurrence of voltage sags, the structure can regulate the DC bus voltage in the established reference value, ensuring high power factor even during AC mains power supply disturbances. One can emphasize that these operational characteristics, in addition of being achieved with the switched converters that comprise the structure processing only an amount of the total output power, was observed that the whole assembly is more efficient and robust. The proposed structure is an excellent alternative for supplying high power DC loads sensitive to disturbances caused by AC mains and for applications involving voltage oscillations compensation due to intermittences of microgeneration systems that are connected to DC distribution of microgrids.